A new collocation method for solving some first-order differential models of biological systems - Mufutau Ajani Rufai; Bruno Carpentieri; Aisha Abidemi Alimi; Mariam Abiodun Babalola (Scientific African)
In this research paper, we propose a new collocation method (NCM) that provides more accurate numerical solutions to initial value problems (IVPs) of ordinary differential equations (ODEs) models of biological systems. To evaluate the performance of the proposed method, we conduct numerical examples on various differential model problems relevant to biological systems. Specifically, the NCM is used to obtain more accurate numerical solutions to three different models: logistic growth, SIR, and Lotka–Volterra. This work demonstrates that the NCM outperforms some existing numerical methods in the literature, thereby establishing its superior efficiency and effectiveness in solving real-world problems in the form of first-order ODE models in the domain of computational and mathematical biology. The proposed NCM method contributes to developing advanced numerical methods for solving some biological systems models.